Pengaruh Political Connection terhadap Cumulative Abnormal Return dan Trading Volume Activity pada Pemilihan Presiden 2019 - Eldam Pradana; Sudrajat; Pigo Nauli; Yuliansyah Yuliansyah (Penerbit Goodwood, 2021)
Purpose: This study aimed to identify the impact of Political Connection on Cumulative Abnormal Return (CAR) and Trading Volume Activity (TVA) for companies that associate with political figures in the presidential election of 2019. Research methodology: This study used quantitative methods, with a population of 25 companies on the Indonesian stock exchange, through daily stock prices. Result: This investigation showed no significant difference in the Cumulative Abnormal Return between before and after the announcement of the Constitutional Court. Then, there was no significance value on Trading Volume Activity and Cumulative Abnormal Return between before and after the announcement of General Election Commissions. Limitations: In this study, the limitation is observation time which is only 36 days. The number of samples is limited, which only 25 companies with the scope of research of companies that have affiliations with the winners of the 2019 general election. Contribution: This research implicates companies affiliated with politics. This is in the 2019 general election against the winners of the general election in 2019.